Mechanism and efficacy of virus inactivation by a microplasma UV lamp generating monochromatic UV irradiation at 222 nm. (1st November 2020) - Oh, Chamteut; Sun, Peter P.; Araud, Elbashir; Nguyen, Thanh H.
Highlights: Microplasma UV lamp (monochromatic at 222 nm) was applied to inactivate AdV type 2. PCR-based molecular assays were developed to study inactivation mechanisms. Capsid proteins were the primary target for monochromatic UV irradiation at 222 nm. Microplasma UV showed 4.4 times higher inactivation efficacy for AdV type 2 than LPUV. Abstract: This study evaluated the potential of a microplasma UV lamp as an alternative UV source to the current mercury-based (Hg-based) UV lamp for water disinfection. We developed a set of PCR-based molecular assays (long-range qPCR, DNase, and binding assay) to quantify the adenovirus genome, capsid, and fiber damage with a wide detection range (10 0.5 -10 6.5 PFU/mL). We used these molecular assays to characterize adenovirus (AdV) inactivation kinetics by microplasma UV that produced monochromatic UV at 222 nm. We found that the inactivation rate constant (0.142 cm 2 /mJ) due to microplasma UV was 4.4 times higher than that of low-pressure Hg UV (0.032 cm 2 /mJ). This high efficacy was attributed to monochromatic UV wavelength at 222 nm damaging the AdV capsid protein. The results of these molecular assays also proved that microplasma UV and medium-pressure Hg UV with a bandpass filter at 223 nm (MPUV223nm ) have a similar influence on AdV (p>0.05). We then estimated the relative energy efficiency of MPUV and microplasma UV to LPUV for 4 log reduction of the viruses. We found that the microplasma UV resulted in higher inactivation rate constants for viruses than the current Hg-based UV. Consequently, microplasma UV could be more energy efficient than low-pressure Hg UV for water disinfection if the wall-plug efficiency of the microplasma UV lamp improved to 8.4% (currently 1.5%). Therefore, the microplasma UV lamp is a promising option for water disinfection. Graphical abstract: Image, graphical abstract